Aiming Big with Small Cars Emergence of a Lead Market in India - Tiwari, Rajnish; Herstatt, Cornelius; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book focuses on the small car segment of India's automotive industry to explain the emergence of lead markets. The authors contend that the current understanding of lead markets does not sufficiently explain the business practices that are born out of the intensified globalization of innovation. Lead markets are considered crucial for the global diffusion of new products and this book investigates whether sustainable lead markets can also emerge in developing economies, and if so, under which conditions. The authors question the conventional wisdom and propose updates and extensions to the lead market theory to better reflect the changing ground realities on ground.
1.Setting the Scene: The Changing Innovation Landscape -- 2.Developing Countries and Innovation: Innovation Opportunities Spread Globally -- 3.Exploring Opportunities for Global Innovation: Contribution of the Lead Market Strategy -- 4.Growing Demand for Affordable Solutions: India as an Emerging Hub for Frugal Designs -- 5.Need for a Rethink: Challenging the Conventional Wisdom on Innovation Strategies -- 6.Investigating India's Small Car Industry: Emergence of a Lead Market for Frugal Designs -- 7.Profile of India's Automobile Industry -- 8.Role of Small Cars in India's Passenger Car Segment -- 9.Shaping the Context -- 10.Conclusions.
Keywords: Business; Leadership; Management; Industrial management; Globalization; Markets; Automotive engineering; Economic policy; Business and Management; Innovation/Technology Management; Emerging Markets/Globalization.; R & D/Technology Policy; Business Strategy/Leadership.; Automotive Engineering